2003
DOI: 10.1523/jneurosci.23-05-01949.2003
|View full text |Cite
|
Sign up to set email alerts
|

Serum Transthyretin Monomer as a Possible Marker of Blood-to-CSF Barrier Disruption

Abstract: The CNS is shielded from systemic influences by two separate barriers, the blood-brain barrier (BBB) and the blood-to-CSF barrier. Failure of either barrier bears profound significance in the etiology and diagnosis of several neurological diseases. Furthermore, selective opening of BBB tight junctions provides an opportunity for delivery of otherwise BBB impermeant drugs. Peripheral assessment of BBB opening can be achieved by detection in blood of brain-specific proteins that extravasate when these endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
2
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 35 publications
3
92
2
4
Order By: Relevance
“…A second, more direct route is provided by disruptions on the capillary level that allow drainage of perivascular S100␤ directly into the circulation. 11,21 The second route is more likely in patients with brain tumors or other lesions. Finally, markers other than S100␤ may indicate CSF-to-BBB dysfunction better.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second, more direct route is provided by disruptions on the capillary level that allow drainage of perivascular S100␤ directly into the circulation. 11,21 The second route is more likely in patients with brain tumors or other lesions. Finally, markers other than S100␤ may indicate CSF-to-BBB dysfunction better.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were drawn before (10 minutes prior to mannitol injection), during (45 seconds, 1 minute, and 10 minutes after mannitol injection), and after (up to 6 hours) iatrogenic, selective, intraarterial osmotic opening of the BBB. 11,20,21 A total of 54 BBBD procedures in 6 patients were studied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are attributable to protein denaturation during SDS-PAGE, which hampers differentiation between the CSF-specific monomeric form and the tetrameric form present in blood (38 ). This distinction would require more sophisticated techniques (39 ) that are unlikely to become routine procedures but may be helpful in difficult situations, e.g., in the case of blood contamination.…”
Section: Clinical Chemistrymentioning
confidence: 92%
“…Failure of either barrier bears profound significance in the etiology and diagnosis of several neurological diseases. Comparative proteome analysis of sera from patients undergoing BBB disruption (BBBD) with pre-BBB opening serum indicated that alpha-2-macroglobulin (A2MG) and TTR were correlated with BBBD and may be a peripheral tracer of BCB [256,257]. In Alzheimer's disease (AD) patients, serum proteins such as HG, hemoglobin, vitronectin, alpha-1-acid glycoprotein (A1AG), apo B100, fragment of factor H, and histidine-rich glycoprotein were found at altered levels [258].…”
Section: Application To Human Disease Detectionmentioning
confidence: 99%